My friend Dahmer : a graphic novel - Backderf, Derf. 1959- (Abrams ComicArts, 2012)
In 1991, Jeffrey Dahmer, the most notorious serial killer since Jack the Ripper, seared himself into the American consciousness. To the public, Dahmer was a monster who committed unthinkable atrocities. To Derf Backderf, 'Jeff' was a much more complex figure: a high school friend with whom he had shared classrooms, hallways, and car rides. In [this story], a haunting and original graphic novel, writer-artist Backderf creates a surprisingly sympathetic portrait of a disturbed young man struggling against the morbid urges emanating from the deep recesses of his psyche-- a shy kid, a teenage alcoholic, and a goofball who never quite fit in with his classmates. With profound insight, what emerges is a Jeffrey Dahmer that few ever really knew, and one readers will never forget."--Amazon.com.